Inducible glutathione S-transferase (IrGST1) from the tick Ixodes ricinus is a haem-binding protein. (April 2018) - Perner, Jan; Kotál, Jan; Hatalová, Tereza; Urbanová, Veronika; Bartošová-Sojková, Pavla; Brophy, Peter M.; Kopáček, Petr
Abstract: Blood-feeding parasites are inadvertently exposed to high doses of potentially cytotoxic haem liberated upon host blood digestion. Detoxification of free haem is a special challenge for ticks, which digest haemoglobin intracellularly. Ticks lack a haem catabolic mechanism, mediated by haem oxygenase, and need to dispose of vast majority of acquired haem via its accumulation in haemosomes. The knowledge of individual molecules involved in the maintenance of haem homeostasis in ticks is still rather limited. RNA-seq analyses of the Ixodes ricinus midguts from blood- and serum-fed females identified an abundant transcript of glutathione S-transferase ( gst ) to be substantially up-regulated in the presence of red blood cells in the diet. Here, we have determined the full sequence of this encoding gene, ir-gst1, and found that it is homologous to the delta-/epsilon-class of GSTs. Phylogenetic analyses across related chelicerates revealed that only one clear Ir GST1 orthologue could be found in each available transcriptome from hard and soft ticks. These orthologues create a well-supported clade clearly separated from other ticks' or mites' delta-/epsilon-class GSTs and most likely evolved as an adaptation to tick blood-feeding life style. We have confirmed that Ir GST1 expression is induced by dietary haem(oglobin), and not by iron or other components of host blood. Kinetic properties of recombinant Ir GST1 were evaluated by model and natural GST substrates. The enzyme was also shown to bind haemin in vitro as evidenced by inhibition assay, VIS spectrophotometry, gel filtration, and affinity chromatography. In the native state, Ir GST1 forms a dimer which further polymerises upon binding of excessive amount of haemin molecules. Due to susceptibility of ticks to haem as a signalling molecule, we speculate that the expression of Ir GST1 in tick midgut functions as intracellular buffer of labile haem pool to ameliorate its cytotoxic effects upon haemoglobin intracellular hydrolysis. Graphical abstract: Highlights: Haem-inducible Ir GST1 from Ixodes ricinus is the first functionally characterised tick GST of delta-/epsilon-class. Ir GST1 and its orthologues from other ticks form a distinct clade of GSTs evolved as an adaptation to hematophagy. Expression of Ir GST1 in tick gut is induced by host haem, but not by host iron. Ir GST1binds haemin in vitro and is presumably an endogenous intracellular scavenger of excessive haem.